Participatory planning of the future of waste management in small island developing states to deliver on the Sustainable Development Goals. (20th June 2019) - Fuldauer, Lena I.; Ives, Matthew C.; Adshead, Daniel; Thacker, Scott; Hall, Jim W.
Abstract: Waste management is particularly challenging for Small Island Developing States (SIDS) due to their high per-capita infrastructure costs, remoteness, narrow resource bases and high dependence on tourism. The lack of integrated planning frameworks considering these SIDS-characteristics has stalled progress on sustainable waste management. To address this challenge, this paper proposes an integrated methodology for long-term waste management planning to deliver on the United Nations' Sustainable Development Goals (SDGs) in SIDS. This explicitly combines multi-level participatory SDG visioning and back-casting with waste infrastructure modelling. This methodological development is piloted using a national-scale demonstration on Curacao. Three island-specific waste management portfolios (Inaction, Circular Economy, Technology-led), developed through stakeholder back-casting, are modelled for SDG delivery using a national accounting model under different socio-economic futures. The results highlight the importance of waste prevention and material re-use strategies within islands that engage local populations. Evidence-based identification and evaluation of waste management strategies, grounded in participatory processes, can itself contribute to SDG delivery. Highlights: Infrastructure planning for sustainable development is a complex, uncertain process. Small Island Developing States (SIDS) have special waste infrastructure challenges. A participatory approach to model waste investments on sustainability indicators. The modelling part enhances robustness by considering uncertain futures. The participatory part enables data collection and feasibility of waste investments. Sustainable waste management in SIDS requires drastic demand reduction.